2013
DOI: 10.7482/0003-9438-56-063
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of calves' rearing parameters in two different housing systems: indoor versus outdoor hutches

Abstract: Abstract. The main aim of the study was to compare the rearing effect of calves kept outdoor in individual hutches and indoor in group pens. During the experiments, the following measure ments were carried out: body weight, daily gains, feed intake, morbidity and mortality. The study was conducted on 90 calves from 5th to 90th day of age; all calves were fed the same feed and according to the same schedule. Results revealed that during the first month, the calves from both groups achieved the same daily gains.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
(22 reference statements)
1
1
0
Order By: Relevance
“…It was observed in this study that calves housed separately were less diseased than calves housed aggregately. Similar report was documented by Pereira et al (2014), Wójcik et al (2013) and Cuttance et al (2017) as group/aggregate housing of pre-weaning calves had positive correlation with the prevalence of calve disease because in group housing system the number of infectious pathogens responsible for the occurrence of the disease were very high. However, Klein-Jöbstl et al (2014) disagree with this study result and stated that grouping/ aggregating large number of calves together was not significantly associated with the appearance of diarrhea on the farm but the number of the calves in the group had significant role in the disease occurrence and transmission among the group members.…”
Section: Discussionsupporting
confidence: 83%
“…It was observed in this study that calves housed separately were less diseased than calves housed aggregately. Similar report was documented by Pereira et al (2014), Wójcik et al (2013) and Cuttance et al (2017) as group/aggregate housing of pre-weaning calves had positive correlation with the prevalence of calve disease because in group housing system the number of infectious pathogens responsible for the occurrence of the disease were very high. However, Klein-Jöbstl et al (2014) disagree with this study result and stated that grouping/ aggregating large number of calves together was not significantly associated with the appearance of diarrhea on the farm but the number of the calves in the group had significant role in the disease occurrence and transmission among the group members.…”
Section: Discussionsupporting
confidence: 83%
“…Calves reared in groups showed higher final live weight than calves reared individually (255 vs. 249 kg, P≤0.05) due to the higher daily weight gain (P<0.001) during the second period (Xiccato et al, 2002). Results of Wójcik, et al (2013) revealed that during the first month, the calves from both groups achieved the same daily gains. However, older calves kept in-door were characterized by better daily gains, feed intake and as a result, body weight.…”
Section: Discussionmentioning
confidence: 91%